(untitled) (Historia, 2021)
This study is based on the literature and the author’s experiences as an archivist as well as being a member of the Executive Board of the East and Southern Africa Regional Branch of the International Council on Archives (ESARBICA). The scope of the discussion is limited, geographically, to Angola, Botswana, Democratic Republic of Congo, Kenya, Lesotho,Mozambique, Malawi, Mauritius, Namibia, Seychelles, South Africa,Swaziland, Tanzania, Uganda, Zambia,Zanzibar and Zimbabwe. Most of these countries are members of ESARBICA. Like its mother body the International Council on Archives, one ofESARBICA’s major objective is to promote.